The Effects of a Diet and Exercise Program for Older Adults With Metabolic Syndrome. Issue 3 (September 2015) - Lin, Yu-Hua; Chu, Li-Ling; Kao, Chia-Chan; Chen, Tai-Been; Lee, I; Li, Hui-Chi
ABSTRACT: Background: The prevalence of metabolic syndrome is high among older adults in Taiwan. However, few studies have studied the effect of a combined diet and exercise program on managing metabolic syndrome (MetS) in individuals 65 years and older and living in Taiwan's rural areas. Purpose: This study tests the effectiveness of a diet and exercise program on the MetS biomarkers in older community residents with MetS. Methods: This study used a quasiexperimental study design. All participants were 65 years and older and were diagnosed with MetS. The outcome variables included biomarkers (blood pressure, waist circumference, hip circumference, body mass index, blood sugar, cholesterol, and triglycerides) and demographic characteristics. The participants were distributed into a diet-and-exercise group ( n = 163) and a nondiet-and-nonexercise group ( n = 138). The outcome variables were examined 3 months after the start of the intervention program. Results: The participants in the diet-and-exercise group had lower values than the nondiet-and-nonexercise group for blood pressure, waist circumference, hip circumference, body mass index, blood sugar, cholesterol, and triglyceride (all p s < .001). Conclusions/Implications for Practice: The diet and exercise program is an effective intervention for treating older individuals with MetS. Clear and concise information concerning the effects of diet and exercise in promoting the health of older residents with MetS is helpful to improve the health of the older adults inTaiwan.